The International Criminal Court and its potential to prevent human rights violations : with special consideration to the actual African situation - Hofmann, Ronald (2014)
Includes bibliographical references.This work looks exclusively at future-oriented elements of the purposes of criminal punishment. It examines in particular the impact of the ICC on human rights, especially on the African continent. The main problem in this context is to define clearly such a possible positive impact on the human right situation and to establish proof of it. In the absence of a proof of such a positive impact in the past, the present or the foreseeable future, the justifying of the ICC from an African perspective or in general is in question